Do Thai Physicians Recommend Seasonal Influenza Vaccines to Pregnant Women? A Cross-Sectional Survey of Physicians’ Perspectives and Practices in Thailand - Praphasiri, Prabda; Ditsungneon, Darunee; Greenbaum, Adena; Dawood, Fatimah S.; Yoocharoen, Pornsak; Stone, Deborah M.; Olsen, Sonja J.; Lindblade, Kim A.; Muangchana, Charung (PloS one, 2017)
Physicians play a major role in influencing acceptance and uptake of vaccines. However, little is known about physicians' perspectives on influenza vaccination of pregnant women in Thailand, for whom vaccine coverage is estimated at <1%. In 2013, a self-administered questionnaire on physicians' perceptions, attitudes and practices related to influenza vaccination for pregnant women was distributed to 1,134 hospitals with an antenatal care clinic (ANC) in Thailand. At each hospital, one physician working at the ANC completed the survey. Predictors of routine recommendation of influenza vaccine were analyzed utilizing log-binomial regression. A total of 580 (51%) complete responses were received from physicians practicing at ANCs. A favorable attitude towards vaccination was expressed by 436 (75%) physicians, however only 142 (25%) reported routinely recommending influenza vaccine to pregnant women in their current practice. Physicians were more likely to recommend influenza vaccine routinely when they had more than three years of practice (prevalence ratio [PR] 1.9, 95% CI 1.2-2.3), had treated pregnant women for influenza (PR 1.8, 95% CI 1.3-2.7), perceived the influenza vaccine to be effective (moderate level: PR 1.6, 95% CI 1.1-2.4; high level: PR 1.9, 95% CI 1.3-2.9) and were aware of the Ministry of Public Health's (MOPH) recommendation of influenza vaccination in pregnancy (PR 1.3, 95% CI 1.1-1.7). Vaccine not being available, perception that policy was ambiguous and lack of awareness of MOPH recommendations were the most commonly cited barriers to routine recommendation of influenza vaccine. Despite a national policy to vaccinate pregnant women for influenza, only 25% of Thai physicians working in ANCs routinely recommend vaccination. Strategies are needed to increase vaccine availability and free vaccine services, address clinician concerns over vaccine effectiveness and expand healthcare provider awareness of MOPH recommendations.